Eco-Translation: Raising Ecolinguistic Awareness in Translation - Laura Diamanti (MediAzioni, 2022)
This contribution investigates early theories of Ecological Linguistics (Haugen 1972) and Ecosophy (Naess 1989), and current perspectives (Eliasson and Jahr 1997; Fill 2001, 2018; Steffensen and Fill 2014; Finke 2014; Stibbe 2014) along with the domain of Translation Studies (Lefevere 1992; Tymoczko 2010, 2014) to approach the concept of Ecological Translation (Cronin 2017, 2021; Scott 2015, 2018). A holistic perspective (Mühlhäusler 2000) is considered, which also takes into account the phenomenon of language contact (Ludwig, Mühlhäusler, Pagel, 2018), with regard to the translational practice. Different areas of studies are explored to reflect on the implications of English as a global language, which exerts its dominant impact over non-dominant languages, by effecting their disappearance and loss of cultural identity (Cronin 2003; Mühlhäusler 1996; Kachru 1986, 1992, 1994, 1996; Phillipson 1992). A connection between Ecolinguistics and Translation Studies is identified in the Ecosystemic Translation theory (Lynes 2012), encompassing an “ecology of translation” or a “translation of ecology”. In this respect, as an “interdiscipline” operating “as craft” (Cronin 2017), translation is discussed in the process of foreignisation of the source-text language, opposed to that of its domestication in the target-text language. In particular, the need to minoritise translation rather than to assimilate it to elude ethnocentric translation reveals the aim of a “discursive heterogeneity” contrasting with the assimilation of non-dominant linguistic and cultural difference to the dominant language (Venuti 1996; 2008). An analysis of different views is thus offered in favour of an ethical and ecological approach re-thinking the translation process.